Conceptual Metaphor in Daily Spiritual Texts Murli by Brahma Kumaris - Indira Gita Maharani, Putu; Rajeg, I Made (Humanis; Vol 26 No 2 (2022), 2022)
The meaning of the metaphor is understanding as one of the conceptual domain in terms of other conceptual domains. A metaphor is used effortlessly in everyday life, including in a literary work. The aim of this study is able to help people to understand the metaphoric meaning of Murli, a spiritual text written by Brahma Kumaris. The problems of this study discussed based on metaphorical expressions used in daily spiritual texts Murli and the conceptual metaphors motivate the application of the metaphorical expressions in daily spiritual texts Murli. The data of this study is taken from the daily spiritual texts by Brahma Kumaris Murli . The technique that is used to collect the data is the note-taking technique. The metaphor is identified using MIP (Metaphor Identification Process) by Pragglejaz Group This method helps the process of analyzing metaphorical words. The result of this study showed that Murli consists of 16 conceptual metaphors of the structural metaphor, 2 conceptual metaphors of the orientational metaphor, and 3 conceptual metaphors of the ontological metaphor including the personification and 1 conceptual metaphor of the metonymy.